Perencanaan Pembuatan Aplikasi Mobile Revalcon Sampit Menggunakan Metode Net Present Value - Muhamad Firhan Al Farisi; Yudha Adyatma Syifa (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
This study examines the development plan of Revalcon's online motorcycle taxi service to simplify its services by creating a service application. The purpose of this research is to find out whether making this application can increase Revalcon's turnover, to find out that the author uses NPV (Net Present Value) as a tool for decision makers. The data collection process was carried out by interviewing Revalcon's management. The analysis results show that the final value of the test results is higher than the price of making the application. A review of the test results will be very useful for Revalcon's online motorcycle taxi in deciding on making service applications.